Chlorpromazine and dimethyl sulfoxide modulate the catalytic activity of the plasma membrane Ca2+-ATPase from human erythrocyte - Plenge, Luis (Springer US, 2018)
The plasma membrane Ca2+-ATPase (PMCA) removes Ca2+ from the cytosol into the extracellular space. Its catalytic activity can be stimulated by calmodulin (CaM) or by limited proteolysis. We evaluated the effect of chlorpromazine (CPZ) and dimethyl sulfoxide (DMSO) over the hydrolytic activity of PMCA. Activity was monitored in three different forms: native, CaM-activated and proteolyzed by trypsin. CPZ appears to inhibit PMCA without directly interfering with the C-terminal site, since it is affected by CaM and proteolysis. Although the treatment of PMCA with trypsin and CaM produces an activation, it also produces an enzymatic form that is more sensitive to inhibition by CPZ. The same case was observed in the DMSO inhibition experiments. In the absence of CPZ, DMSO produces a progressive loss of activity, but in the presence of CPZ the profile of activity against DMSO changes and produces a recovery of activity, indicating a possible partition of CPZ by the solvent. Increasing Ca2+ concentrations indicated that CPZ interacts with PMCA rather than with CaM. This observation is supported by docking analysis that suggests that the CPZ-PMCA interaction is non-competitive. We propose that CPZ interacts with the state of lower affinity for Ca2 +.